Investigation of transition metal oxides as electrocatalysts for water oxidation - Li, Haiyan (Nanyang Technological University, 2021)
Scalable hydrogen production by water splitting has been given high expectations to satisfy the ever-growing demands for renewable clean energy and cut greenhouse gas emissions. In the past decades, massive research efforts have been made globally to develop highly efficient oxygen evolution electrocatalysts, because of the significant energy loss caused by the slow oxygen evolution reaction (OER) during water electrolysis. Earth-abundant transition metal (TM) oxides emerge as the potential candidates due to their inexpensiveness and promising activity. For science-based catalyst design, gaining fundamental understandings of the oxygen evolution catalysis on transition metal oxides is essential. This thesis first addresses the role of geometric tilting in influencing the catalytic efficiency of FeO6 octahedra. By setting FeO6 octahedra into crystalline environments, including AFeO3 (A = Y, Gd, Pr, and La) perovskites, ZnFe2O4 spinel, and β-FeOOH, a negative correlation is identified between the catalytic performance and the tilting degree of FeO6 octahedra. It is elucidated that FeO6 octahedral tilting changes the Fe-O covalency and therefore varies the catalytic performance of ferrites. Secondly, by a case study of ZnFe2–xCrxO4 (x = 0 - 2), the influential electronic parameter of the octahedrally-coordinated transition metals in spinel-type oxide catalysts is explored. The specific OER activity of ZnFe2–xCrxO4 is found to have a volcano-shaped dependence on the Cr content. It is identified that the metal-oxygen hybridization at active sites (defined as the percentage of O 2p states that hybridize with TM 3d states), which also follows a volcano-shaped trend with the Cr content, governs the OER activity of ZnFe2–xCrxO4. To rationalize the correlations identified between the bulk electronic parameters and the catalytic performance of metal oxides, a deep understanding of how the oxide surfaces catalyse OER is critical. Recently, growing studies have revealed the surface restructuring of some metal oxides under OER conditions. To identify the real active phase for perovskites undergoing surface reconstruction upon water oxidation, cubic SrCoO3-δ perovskites respectively modified by bulk Fe dopant and Fe ions incorporated from the electrolyte are investigated as OER catalysts. It is found that the activity of SrCoO3-δ oxide electrode is sensitive to the electrolyte environment and the two Fe-modified SrCoO3-δ catalysts, with similar surface amorphous layers but different remaining bulk phases, exhibit roughly equal activities. Accordingly, the reconstructed surface, instead of the remaining bulk, is identified to be directly responsible for the measured catalytic performance.